PERANCANGAN LIFESTYLE CENTER DI PONTIANAK - Chandra, Helen Julia; Andi, Uray Fery; Alhamdani, Muhammad Ridha (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
The lifestyle changes of urban communities in the modern era are shaped by technological advancements, globalization, and the daily use of social media. These factors have created new tendencies in public activities, particularly among Generation Z and millennials, driving greater interest in culinary, fashion, sports, and recreational activities. Such trends demand urban spaces that are not only functional but also capable of offering meaningful social experiences as a new spatial concept in the city. In major Indonesian cities, this demand is addressed through lifestyle centers